Cardiomyopathy. Like mother, like daughter? A new phenotype for a MYH7 mutation. (June 2021) - Abreu, Susana M.; Trigo, Conceição; Pinto, Fátima F.
Abstract: We report the case of a six-year-old girl referred to our department due to her mother's diagnosis of hypertrophic cardiomyopathy. Initial evaluation revealed restrictive physiology on echocardiography and cardiac catheterization. Genetic analysis of both mother and daughter revealed the same genetic variant at the MYH7 gene. Notably, although the genetic mutation was the same, the phenotype differed, resulting in different management and prognosis. The daughter received a heart transplant at the age of 20 due to pulmonary hypertension's early development, whereas the mother was under heart failure medical therapy. This case relevance lies in this specific mutation, which to our knowledge, has not been previously associated with restrictive phenotype, but also on the importance of early referral of family members. Highlights: Mutations on the MYH7 gene are associated with different cardiomyopathy phenotypes. Mutation c.1358G>A is rare and mostly associated with hypertrophic cardiomyopathy. This is the first report associating the restrictive cardiomyopathy phenotype to this mutation. Management and prognosis of the two phenotypes can be significantly different.